YIELD OF SUNFLOWER (HELIANTHUS ANNUUS) HYBRIDS DEPENDING ON SOWING DATES IN THE WESTERN FOREST-STEPPE - Lykhochvor, В.; Husak, М. (Bulletin of Lviv National Environmental University. Series Agronomy, 2022)
The researches of sowing dates of sunflower in conditions of sufficient moisture in the Western Forest-Steppe of Ukraine were almost not conducted. To determine the optimal sowing dates of Sumiko and Fausto sunflower hybrids, five sowing dates were studied, namely April 10, April 20, April 30, May 10, May 20. The soil of the experimental plot was gray podzolic light loamy with a humus content of 1.8 %. The content of light hydrolyzed nitrogen was 72 mg, mobile forms of phosphorus and potassium (according to Chirikov’s method) were 84 mg and 87 mg per 1 kg of soil, respectively. The reaction of the soil solution was close to neutral, the pH of the salt extract was 6.0. Hydrothermal conditions were typical for the area, but in April the soil temperature was lower than the average long-term data. The results of the research showed that in the early sowing period on April 10 and 20 sunflower seedlings appeared only in 20–25 days due to low soil temperature, and for sowing in May twice faster – in 10–13 days. Field germination of sunflower hybrid seeds in the researches was high (80.9–92.6 %). It decreased in the early sowing period in April (80.9–86.8 %) and increased in late sowing in May (89.7–92.6 %) in conditions of higher soil temperature. Field germination did not change under the influence of moisture, as its reserves were sufficient at all times of sowing. The highest yield of sunflower was formed during sowing on April 30, in Sumico hybrid it was 3.74 t/ha, in Fausto hybrid 3.58 t/ha. It is also advisable to sow these hybrids on April 20, the difference of the yield from April 30 is within the error of research. Sumico hybrid produces higher yields in the early stages of sowing. The May sowing period leads to a significant reduction of sunflower yield due to a shorter growing season. For sowing on April 10, the yield of Sumico hybrid was 3.32 t/ha, Fausto hybrid – 2.95 t/ha, which was less than the sowing date of April 30 by 0.42 t/ha and 0.63 t/ha, respectively. This is due to the late onset of spring, low temperatures during this period, increasing the period of sowing – seedlings and other adverse conditions. In early spring, it is likely that yields in the early sowing period may be higher. The May sowing period leads to a significant reduction of sunflower yield due to the reduction of the growing season. The lowest yield (2.83–3.12 t/ha) in both sunflower hybrids was obtained at late sowing dates – May 10 and 20. In the variant of sowing in May, the duration of the growing season was reduced, the formation of achenes took place in hot conditions, which led to the decrease of yield.